Peran Akuntansi Lingkungan Dalam Meningkatkan Tanggung Jawab Sosial Perusahaan - Erly Fevilia Angel; Ersi Sisdianto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The role of environmental accounting has become increasingly significant with the growing focus on sustainability and corporate social responsibility (CSR) issues. Environmental accounting serves not only as a tool for recording and reporting but also as a strategic instrument that helps companies identify, measure, and manage the environmental impacts of their operational activities. This study aims to analyze the contribution of environmental accounting in supporting CSR implementation, focusing on how environmental accounting information influences managerial decision-making and stakeholder perceptions. The research employs a qualitative approach through literature reviews and case studies of companies that have implemented environmental accounting in their sustainability reports. The findings indicate that companies consistently applying environmental accounting tend to have better reputations, enhanced public trust, and a demonstrated commitment to sustainability. Moreover, environmental accounting promotes resource efficiency and innovation in business processes. Thus, environmental accounting becomes an integral component in strengthening corporate social responsibility while creating long-term value for both companies and society.